Evaluation of Post Treatment Satisfaction in Orthodontic Patients - Sanket Platia; Mukesh Kumar; Aditi Khanna; Sommya Kumari (Asian Journal of Medical Research, 2019)
Background: The goal of orthodontic treatment is to produce a normal or ideal occlusion. However, there is a large variation in treatment outcome. There are a number of factors that may influence patient satisfaction; this includes physical comfort, emotional support, patient expectations and respect for their preference. The aim of the study was to assess the level of satisfaction of orthodontic patients after the treatment. Subjects and Methods: This study design involved a cross-sectional study of 170 orthodontic patients in the final stage of their orthodontic treatment. Results: Study show that a higher percentage of the participants reported that self-motivation was the main reason to go and see the orthodontist. A significantly high percentage of female patients reported that aesthetics was the main reason for seeking orthodontic treatment with more than half of the participants saying that they were very satisfied. Furthermore, 58% of the participants reported that orthodontic treatment improved their confidence and communication skills with no complications during the treatment. Conclusion: The overall response to the questionnaire revealed that, in general, patients who undergone orthodontic treatment remained satisfied with their facial aesthetics in a long-term period after the treatment was done.